OPTIMASI KONSENTRASI INOKULUM, RASIO C:N:P DAN pH PADA PROSES BIOREMEDIASI LIMBAH PENGILANGAN MINYAK BUMI MENGGUNAKAN KULTUR CAMPURAN - Zam, Syukria Ikhsan (El-Hayah : Jurnal Biologi, 2010)
The purposes of this research were to obtain the best inoculum concentration, C:N:P ratio, and pH, and also to identify the ability of mixed culture of hydrocarbonoclastic bacteria in  oil waste degradation. The isolats were used are Acinetobacter baumanni, Alcaligenes eutrophus, Bacillus sp1., Methylococcus capsulatus, Bacillus sp2., Morococcus sp., Pseudomonas diminuta, Xanthomonas albilineans, Bacillus cereus and Flavobacterium branchiophiia. Variation of inoculum concentrations were 10%, 15%, and 20% (v/v), C:N:P ratios were 100:10:1, 100:10:0,5, 100:5:1, and 100:5:0,5, and pH were 6,5, 7,0, 7,5. Observed parameters in optimization were Total Plate Count (TPC) the culture every 24 hours, Total Petroleum Hydrocarbon (TPH) and Chemical Oxygen Demand (COD) examined at the end of the bioremediation period. Best optimization result then analyzed with GC/MS. Optimization result indicated the best inoculum concentration was 10% with TPH degradation 61,79% and COD slope 61,75%. It is assumed that the low value of TPH degradation and COD slope at 15% and 20% inoculum concentration were caused by competition inside the bacterial population at that high inoculum concentration. The competition result in low growth and degradation. C:N:P ratio was 100:5:1 with TPH degradation 66,55% and COD slope 85,18%. It is assumed that the C:N:P ratio is equal, so it can enhance the bioremediation procces. The best pH was 7,5 with TPH degradation 73,24% and COD slope 86,28%. The process at the optimum conditions using inoculum as a mixed culture enhanced the bioremediation process with the result as follows, TPH degradation 93,06%, COD 90,73% for treatment. The chromatogram indicated that total hydrocarbon compound from nC9 – nC32 have been degraded by 43,413% – 63,117%. A good result of bioremediation was obtained from mixed culture inoculum at 10% concentration, C:N:P ratio of 100:5:1, and pH 7,5.Keywords:    Bioremediation, hydrocarbonoclastic bacteria, inoculum concentration, C:N:P ratio, pH